Anti-Arthritic Activity of Sanguisorba Minor Subsp. Balearica Against “Freund’s Complete Adjuvant-Induced” Arthritis in Rats - İNAN GENÇ, Aysun; GENÇLER ÖZKAN, Ayşe Mine; ADALI, Orhan (Ankara Universitesi Eczacilik Fakultesi Dergisi, 2023)
Therapeutic properties of Sanguisorba L. genus plants are supported by numerous in vivo and in vitro studies showing the anti-viral, anti-ulcerogenic, anti-cancer, anti-acetylcholinesterase, radioprotective, anti-allergic, and anti-inflammatory activities. The present study was designed to investigate anti-arthritic activity of the “Sanguisorba minor subsp. balearica (Bourg. ex Nyman) Muñoz Garm. & C.Navarro” (Smb), a subspecies of Sanguisorba L. genus, on CFA-induced arthritic rat model. The extract of aerial parts of the Smb was obtained by the consecutive steps of maceration process. The phytochemical content of the extract was analyzed by the High Performance Liquid Chromatography (HPLC) method. Complete Freund’s Adjuvant-induced arthritic rats were used to examine the anti-arthritic activity of the plant extract. HPLC analysis revealed high amount of phenolic compounds in the Smb extract. The identified phenolics are ellagic acid, gallic acid, quercetin dehydrate and p-coumaric acid with the concentrations of 4,1288; 2,6342; 0,0871 and 0,0633 ppm, respectively. Injection of Smb extract to rats caused a decrease in paw thickness in the CFA-induced arthritic animals. The decrease in paw thicknesses of animals treated by quercetin and Smb 70 mg/kg groups was higher than diclofenac sodium group. Smb 34 mg/kg group also showed a decrease in paw thickness but it was lower compared to quercetin and Smb 70 mg/kg groups and higher than the diclofenac sodium group. According to the histopathological evaluations of the joint tissues, both 34 mg/kg and 70 mg/kg Smb extract treatment of animals were improved inflammatory deformations related to arthritis.
Keywords: 3. Good health